Mechanical design of a quadruped robot for horizontal ground to vertical wall movement - Sh. I. Alsalameh, Abd Alsalam; H.M. Amin, Shamsudin; Mamat, Rosbi (2000)

(untitled)
In this paper, an emphasis is given towards the mechanical structure of a quadruped robot which is able to walk on ground, climb on vertical walls, and perform the ground-wall-movement automatically. An overview of the robot is shown and the configuration, number of DOFs, and actuation system of the leg are analyzed. The biologically inspired gaits of the robot are discussed. The movement of the leg from the ground to the wall is analyzed. The integrated leg movement-trunk regulation sequences are simulated. The trajectories of specific points on the trunk are traced, showing the limits for safe movement inside meandrous chimneys or zigzag tubing